At home elsewhere the transnational Kapamilya imaginary in selected ABS-CBN station IDs - Cabalquinto, Earvin Charles B. (Plaridel, 2014)
Access online though this link: https://www.plarideljournal.org/article/at-home-elsewhere-the-transnational-kapamilya-imaginary-in-selected-abs-cbn-station-ids